Information governance as a socio-technical process in the development of trustworthy healthcare AI - Rees, Nigel; Holding, Kelly; Sujan, Mark (Frontiers in Computer Science, 2023)
In this paper we describe our experiences of managing information governance (IG) processes for the assurance of healthcare AI, using the example of an out-of-hospital-cardiac-arrest recognition software within the context of the Welsh Ambulance Service. We frame IG as a socio-technical process. IG processes for the development of trustworthy healthcare AI rely on information governance work, which entails dialogue, negotiation, and trade-offs around the legal basis for data sharing, data requirements and data control. Information governance work should start early in the design life cycle and will likely continue throughout. This includes a focus on establishing and building relationships, as well as a focus on organisational readiness and deeper understanding of both AI technologies as well as their safety assurance requirements.